Mono- and Ditopic Bisfunctionalization of Graphene - Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2016)
For the first time, the bisfunctionalization of graphene by employing two successive reduction and covalent bond forming steps is reported. Bulk functionalization in dispersion and functionalization of individual sheets deposited on surfaces have both been carried out. Whereas in the former case attacks from both sides of the basal plane are possible and can lead to strain-free architectures, in the latter case, retrofunctionalizations can become important when the corresponding anion of the addend is a sufficiently good leaving group.
Keywords: functionalization; graphene; Raman spectroscopy; retrofunctionalization; topicity